Дослідження впливу вуглецевих нанотрубок на протопласти тютюну для створення нових підходів у біотехнології рослин - Бурлака, О.М.; Пірко, Я.В.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. In order to develop the background for the creation of novel carbon nanotubes (CNTs) based approaches in plant biotechnology the effect of non-covalently functionalized single-walled and multi-walled CNTs (SWCNTs and MWCNTs, respectively) on tobacco Nicotiana tabacum L. mesophyll protoplasts was investigated. Factors influencing the viability of protoplasts exposed to CNTs, namely dose, CNTs type, functionalization type, were determined. Methods. Physical and chemical CNTs surface modification methods, in vitro plant culture approaches and microscope studies were combined to evaluate the effect of CNTs on protoplasts. Results. The dose-dependent adverse impact of CNTs on viability of protoplasts was observed. However protoplasts demonstrated higher viability when exposed to SWCNTs in compere to MWCNTs. Absence of change in protoplasts viability was observed when protoplasts were exposed to identical concentrations of CNTs functionalized using different molecules, indicating equal biological compatibility of all three types of used functionalization coatings. Keywords: carbon nanotubes – CNTs, functionalization, protoplasts, plant biotechnology.